Implementasi Keterlibatan Orang Tua dalam Proses Pembelajaran di TKIT RAUDHATUL JANNAH Cilegon Banten - Fauziyyah, Fauziyyah; Lestariningrum, Anik (Efektor, 2024)
Early childhood education is a critical stage in building a holistic foundation for a child's development. In this context, parental involvement plays a vital role in supporting the child's learning process at school. This study aims to explore the role and implementation of parental participation in the learning process at TKIT Raudhatul Jannah, Cilegon, Banten. Parental involvement is considered crucial for supporting the holistic development of early childhood and ensuring their readiness for the next educational level. This study employs a qualitative method with a case study approach, where data were collected through in-depth interviews, participatory observation, and documentation. The data analysis technique used is triangulation, which allows for validating information from various sources to obtain a comprehensive understanding. The findings reveal that parental participation at TKIT Raudhatul Jannah significantly enhances the children's learning process. Forms of involvement include participation in regular meetings, parenting programs, school activities, as well as support for learning at home. The positive impact of this involvement is evident in the increased motivation to learn, socio-emotional development, and academic readiness of the children. The synergy between parents and the school also supports the implementation of the *Kurikulum Merdeka* (Independent Curriculum), which emphasizes experiential learning. This study highlights the importance of strong collaboration between schools and parents to achieve comprehensive success in early childhood education.